Laser‐Assisted Lip Repositioning With Smile Elevator Muscle Containment and Crown Lengthening for Gummy Smile: A Case Report. Issue 3 (22nd April 2019) - Ganesh, Balaji; Burnice, Nalina Kumari C.; Mahendra, Jaideep; Vijayalakshmi, Rajaram; K., Anil Kumar
Abstract : Introduction: Treating the patients with excessive gingival display to provide a pleasant smile is a challenge to the periodontist. Gummy smile can be due to excessive vertical bone growth, dentoalveolar extrusion, short upper lip, upper lip hyperactivity, or altered passive eruption. Gummy smile associated with hyperactivity of smile elevator muscles can be treated by surgical techniques like lip repositioning, botulinum toxin injection, lip elongation with rhinoplasty, detachment of the lip muscles, and myectomy. Regardless of the technique used, to achieve a predictable result with long‐term stability limiting upper lip movement when the patient smiles, firm muscle containment is imperative. Case Presentation: The case report describes the excessive gingival display having a multifactorial etiology in a 25‐year‐old female patient. Altered passive eruption in upper anterior teeth was treated by crown lengthening followed by management of hyperactive lip using a diode laser‐assisted lip repositioning along with traction and muscle containment. Excellent and predictable results were obtained after a 1‐year follow‐up without the relapse of gummy smile. Conclusions: The case report showed an excellent result when treated by a combined approach of an innovative procedure with laser‐assisted lip repositioning aimed at maintaining the traction and containment of the smile elevator muscles along with crown lengthening procedure by gingivectomy.